Nacho and Lolita - Ryan, Pam Muñoz (Scholastic Press, 2005)
A very rare pitacohi bird falls in love with a swallow and plucks his colorful feathers to transform dry, barren San Juan Capistrano into a haven of flowers and flowing water, which the swallows can easily find when returning from their annual migration.